Effectiveness Of Floor Cleaning And Wall Cleaning On Growth Of Pathogen Germs In The Current Room Of Dr. Kariadi Hospital, Semarang - Linawati Neny Yunitasari; Elyana Sri Sulistyowati; Hadiharti Wahyuningtyas (Sekolah Tinggi Ilmu Kesehatan (STIKes) Karya Husada Semarang, 2023)
Surface swab examination is carried out to evaluate the cleaning that has been carried out both in detecting the presence of germs in the environment and also for checking the count of germ colonies on the floor surface. The results of the preliminary study by looking at the results of floor swab measurements after general cleaning, especially floor cleaning, obtained data from March - May 2022, 113 outpatient rooms, inpatient and operating rooms and found results that did not meet the quality standards for floor swabs, there were 33 rooms, namely operating room, central nutrition, delivery room, baby room, cardiac catheterization room, mortuary, Rajawali pharmacy, CSSD room, PBRT room, Garuda room, Kepodang and registration room. The aim is to determine the effectiveness of cleaning floors and walls against the growth of pathogenic germs in the Heart Installation. Quantitative research method which is descriptive analytic, test analysis using paired t-test and Wilcoxon. Results: there is no significant difference between cleaning the floor on the growth of pathogenic germs in Pre-post General Cleaning, namely 0.678. Floor Cleaning First-Second 3.5 Hours is 0.259. Keywords: pathogenic germs; floor cleaning; wall cleaningEfektifitas Pembersihan Lantai Dan Pembersihan Dinding Terhadap Pertumbuhan Kuman Patogen Di Ruang Rawat RSUP Dr Kariadi SemarangABSTRAK Pemeriksaan swab permukaan dilakukan untuk mengevaluasi pembersihan yang telah dilakukan baik dalam mendeteksi keberadaan kuman yang ada dilingkungan dan dilakukan juga pemeriksaan hitung koloni kuman permukaan lantai. Hasil studi pendahuluan dengan melihat hasil pengukuran swab lantai setelah dilakukan general cleaning khususnya pembersihan lantai didapatkan data pada bulan Maret - Mei 2022, 113 ruang rawat jalan, rawat inap dan kamar operasi dan ditemukan hasil yang tidak memenuhi syarat baku mutu usap lantai ada 33 ruang yaitu kamar operasi, gizi sentral, ruang bersalin, kamar bayi, ruang keteterisasi jantung, kamar jenazah, farmasi Rajawali, ruang CSSD, ruang PBRT, ruang Garuda, Kepodang dan Ruang pendaftaran. Tujuan untuk mengetahui efektifitas pembersihan lantai dan dinding terhadap pertumbuhan kuman pathogen di Instalasi Jantung. Metode Penelitian kuantitatif yang bersifat deskriptif analitik, analisa uji menggunakan paired t-test dan wilcoxon. Hasil : tidak ada perbedaan signifikan antara pembersihan lantai terhadap pertumbuhan kuman pathogen pada Pre-post General Cleaninng yaitu 0,678. Pembersihan Lantai 3,5 Jam Pertama-Kedua yaitu 0,259. Kata kunci : kuman pathogen; pembersihan lantai; pembersihan dinding